Correlation of Middle Upper Arm Circumference With Other Anthropometric Indictors and Cardiovascular Disease Risk Factors in Young Adults of Urban Areas of Hyderabad, Pakistan - Baig, Nimra Masood; Samo, Ayaz Ali; Narejo, Naeem Tariq; Kalhoro, Hameeda (BioSight, 2023)
Introduction: Middle Upper Arm Circumference (MUAC) is used to assess nutritional status particularly under nutrition. Recently, the use of MUAC has been suggested as a novel anthropometric marker to assess the condition of obesity among the children, adolescents, and young adults. We, therefore, setup / study to evaluate the correlation of MUAC for the assessment of various CVD risk factors. Methodology: The study was carried out from April 2021 to March 2022. Total 366 participants were randomly selected, out of which 190 were male participants and 176 were female participants. The data was collected using interview based questionnaire; middle upper arm circumference was measures using a non stretchable measuring tape. Statistical analysis was done using SPSS ver 23. Results: The mean age of participants was 24.04±4.04, the mean values of WC, WHR, SBP, DBP, and LDL were significantly higher (P< 0.05) in males, the mean values of HDL were significantly higher in females(p< 0.05). Non-significant difference in the mean values of BMI, FBG, Cholesterol and Triglycerides (P> 0.05) were observed between male and female participants. MUAC showed strong positive correlation with BMI, WC and WHR (P<.001). Except HDL all other CVD risk factors showed significant positive correlation with MUAC (P<.001), however, MUAC showed a significantly negative correlation with HDL( r = -.370, P<.001) in males, no correlation of MUAC with HDL ( r = -.028, P<.001) was observed in females. Conclusion: Except HDL significant correlation was observed between MUAC and various CVD risk factors.